Wallerstein 2.0 Thinking and Applying World-Systems Theory in the 21st Century - Jacob, Frank (Sozialtheorie, 2023)
Immanuel Wallerstein's world-systems theory can help to better understand and describe developments of the 21st century. The contributors address the possibilities to reread Wallerstein's theoretical thoughts and ideas that are related to different disciplines in the humanities and social sciences. The presented interdisciplinary approach of this anthology thereby intends to highlight the broader value of Wallerstein's ideas, even almost five decades after the famous sociologist and economic historian first expressed them.